Natural Communication About Uncertainties in Situated Interaction - Pejsa, Tomislav; Bohus, Dan; Cohen, Michael; Saw, Nick; Mahoney, James; Horvitz, Eric (ICMI '14, November 12-16, 2014, Istanbul, Turkey, 2014)
Physically situated, multimodal interactive systems must often grapple with uncertainties about properties of the world, people, and their intentions and actions. We present methods for estimating and communicating about different uncertainties in situated interaction, leveraging the affordances of an embodied conversational agent. The approach harnesses a representation that captures both the magnitude and the sources of uncertainty, and a set of policies that select and coordinate the production of nonverbal and verbal behaviors to communicate the system’s uncertainties to conversational participants. The methods are designed to enlist participants’ help in a natural manner to resolve uncertainties arising during interactions. We report on a preliminary implementation of the proposed methods in a deployed system and illustrate the functionality with a trace from a sample interaction.